Seasonal variations of trace metal chemical forms in bed sediments of a karstic river in Lebanon - Korfali, Samira Ibrahim (2015)
Although Lebanon has abundant water, its rivers are polluted and aquifer water mismanaged. Effective river water usage requires an understanding of the geochemistry of polluting metals in catchments. Climate is “Mediterranean”: wet winters and dry summers. Active sediment flushing is restricted to winter high discharge episodes. Except in winter, water column pollutants are removed by precipitation or sorption to the surface of static bed sediments. Hence (1) does winter flushing of contaminated sediment and replacement by clean sediment favour self purification? (2) does the distribution of metals between extractable fractions change seasonally and thereby affect metal bioavailability ? Results on the distribution of metals are reported for Fe, Pb, Zn, Cu and Cd in bed sediments from Nahr Ibrahim (a karstic river) for summer and winter. A Tessier-like sequential extraction scheme was applied to samples (< 75 μm) for five locations along a 13 km stretch to the sea. Water pH was above 8.2 at all locations implying a very low solubility for Fe. Sediment was derived from catchment soils and limestone. Total sediment Fe increased in winter at all sites following deposition of eroded soil from upstream. Cadmium, Cu and Pb derived from polluting sources; the sources of Zn were more complex. Dilution by clean sediment explained winter reductions in total Cd, Cu and Pb; Zn changes were less consistent. Iron occurred mostly (> 77 sum of fractions) in the residual fraction compared with 6– 31 for pollutants; residual Cu and Zn showed a small increase in winter whereas Cd and Pb did not change. All readily exchangeable metals decreased in winter and the carbonate bound forms predominated in both seasons. Nahr Ibrahim has a high capacity for self purification and metal resolubilisation from sediment will be limited by the solubility of carbonate forms.